A study of efficiency of International Refugee Law in Dealing with Displaced Populations - Dr. Ankur Pare (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The refugee problem today is global, international, multi-dimensional and humanitarian which has challenged the international community and become a classic example of the inter-dependence of the international community. Considering the uncertain status of displaced populations in India and importance of protection of their rights, the researcher has selected the topic “A study of efficiency of International Refugee Law in Dealing with Displaced Populations”. It is found that the satisfaction level of refugees from the initiatives taken at national and international level is found to be high among the refugees.